IDENTIFIKASI MIKROALGA DARI HABITAT RAWA GAMBUT CAGAR BIOSFER GIAM SIAK KECIL BUKIT BATU SEBAGAI RANCANGAN LEMBAR KERJA PESERTA DIDIK MATERI PROTISTA KELAS X SMA - Feni Armadani; Zulfarina Zulfarina; Nursal Nursal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Swamp land is land that occupies a transitional position between land and water. Degradation of swamps is currently common, such as fires which result in a reduction in the area of peat swamps. The consideration of the condition of water stored in peat swamps fosters a unique ecosystem with a diversity of endemic living things such as microalgae. This study was conducted to determine the type of microalgae that was successfully identified from the peat swamp habitat of Giam Siak Kecil Bukit Batu Biosphere Reserve which was used in designing Worksheets Students in the kingdom protista class X SMA material, held from January 2019 to April 2019. This study used a method survey by determining the sampling point using purposive sampling technique. The parameter in this study was the identification of microalgae isolates. The research design consists of 2 stages. The first stage is exploratory research: Taking samples of microalgae water for isolation and identification. The second stage is the design of LKPD in Kingdom X Protista class in high school. The results of the study obtained 3 types of microalgae that were successfully identified from the peat swamp Giam Siak Kecil Biosphere Reserve Bukit Batu, namely Chlorella sp, Chlamydomonas sp, and Navicula sp. The results of this study were subsequently developed into Student Worksheets in the Kingdom Protista class X high school material.Key Words: Identification, Microalgae, Design of LKPD, Peat Swamp